2010
DOI: 10.1001/jama.2010.490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B-Vitamin Therapy on Progression of Diabetic Nephropathy

Abstract: isrctn.org Identifier: ISRCTN41332305.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
165
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(170 citation statements)
references
References 34 publications
3
165
0
2
Order By: Relevance
“…The final fourteen RCT enrolled 39 420 patients. Among them, seven were included in the without folate fortification subgroup (28)(29)(30)(31)(32)(33)(34) , four were included in the with folate fortification subgroup (35)(36)(37)(38) and three were included in the partial folate fortification subgroup (39)(40)(41) . The screening process of potential articles is summarized in a flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The final fourteen RCT enrolled 39 420 patients. Among them, seven were included in the without folate fortification subgroup (28)(29)(30)(31)(32)(33)(34) , four were included in the with folate fortification subgroup (35)(36)(37)(38) and three were included in the partial folate fortification subgroup (39)(40)(41) . The screening process of potential articles is summarized in a flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wrone et al (13) Righetti et al (14) Zoungas et al (12) House et al (21) Heinz et al (22) Overall 0·159537 One report demonstrated that endothelial cells can develop abnormal vasoreactivity and may adopt a prothrombotic phenotype and secrete leucocyte chemotactic factors, adhesion molecules and inflammatory cytokines when exposed to elevated Hcy (23) . Endothelial dysfunction is a key process in atherosclerosis, which independently predicts CVD events (24) ; and it becomes progressively more common as renal function declines (25) .…”
Section: Studymentioning
confidence: 99%
“…Also, to the best of our knowledge, there are no studies that have determined a threshold value for Hcy level for effective prevention of cardiovascular events in the general population or in patients with CKD. Observational data in a meta-analysis show that a 25 % reduction in Hcy was associated with a 32 % lower risk of CVD among Study Righetti et al (16) Wrone et al (13) Righetti et al (14) Zoungas et al (12) Jamison et al (20) Nanayakkara et al (18) Vianna et al (17) Mann et al (19) House et al (21) Heinz et al (22) Overall 0·074931 …”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations